Dialectical Behavior Therapy Skills Training With Music Therapy Interventions for Adults With Serious Mental Illness: A Quasi-Experimental Nonequivalent Control-Group Pilot Study. (23rd June 2022) - Dvorak, Abbey; Landeck, Lindsey; Dyer, William; Spiegel, Deborah
Abstract: Dialectical behavior therapy (DBT) improves emotion regulation by building skills in mindfulness, distress tolerance, emotion regulation, and interpersonal effectiveness. The purpose of this pilot study was to compare a DBT skills group with a combined DBT skills and music therapy (MT) group on participant outcomes of attendance, participation, skill practice, and skill knowledge, as well as determine feasibility of study procedures. We used a quasi-experimental nonequivalent control-group design with all groups co-led by a psychologist and a music therapist. Clinicians facilitated twice weekly 45-min groups in 12-week cycles for a total of eight groups over 2 years. The groups alternated DBT-only and DBT+MT; participant data were analyzed for their first cycle attended. The DBT-only group followed a standard DBT skills training format, whereas the DBT+MT group included music therapy interventions as group exercises. Participants ( N = 26) were adults with serious mental illness referred to the inpatient psychosocial rehabilitation group (PSR) at a state psychiatric hospital. Participants completed a demographic form, diary cards, and exit interview; clinicians recorded attendance and session participation. Participants in the DBT+MT condition had significantly higher participation levels, slightly higher average attendance, submitted more diary cards, and included more feeling statements than the DBT-only condition. Although interpretations should be approached with caution, the pilot study intervention shows promise. Overall, this study could be implemented as intended under close monitoring, with minor modifications to assist with recruitment and data collection. Modifications, clinical implications, and recommendations for future research are discussed.